Infinite transitivity on the Calogero-Moser space C₂ - Kesten, J.; Mathers, S.; Normatov Z. (Algebra and Discrete Mathematics, 2021)
We prove a particular case of the conjecture of Berest–Eshmatov–Eshmatov by showing that the group of unimodular automorphisms of C[x, y] acts in an infinitely-transitive way on the Calogero-Moser space C₂.